The Political participation in interpersonal relationships within a public hospital - Roso, Elsa Franke; Oliveira, Paulo Antonio Barros (Argumentum, 2021)
This study aims to understand the contributing factors that influenced the political participation of government employees of a specialised state public hospital in Rio Grande do Sul, who distinguished themselves through their capacity to mobilise against a reduction of labour rights imposed by the state government. Using a qualitative exploratory research approach, fourteen civil servants and a union leader were interviewed. It concludes that the hospital workers’ political participation, mediated by both the union and institution collectiveness, was a crucial factor in overcoming the poor visibility of the issue and isolation within the work environment; they engineered interpersonal relationships, guided by notions of solidarity and mutual recognition, as a strategy of resistance in relation to labour insecurity within public service.